Comparative clinical and economic evaluation of polatuzumab vedotin in combination with rituximab, cyclophosphamide, doxorubicin and prednisolone (R-CHP) in the 1st line therapy for adult patients with diffuse large B-cell lymphoma - I. N. Dyakov (Онкогематология)
Aim. To assess the pharmacoeconomic feasibility of using polatuzumab vedotin in combination with rituximab, cyclophosphamide, doxorubicin and prednisolone (R-CHP) in 1st line therapy of adult patients with diffuse large B-cell lymphoma in the Russian healthcare system, taking into account the currently used therapeutic practices in oncohematology.Materials and methods. The design of the study is a retrospective analysis of literature data. Clinical and economic analysis (incremental cost–effectiveness analysis, case-based approach) was performed using sensitivity assessment. The sources of data on the effectiveness of the analyzed drugs were publications on clinical trials, on the cost of drugs – the state register of maximum selling prices, data from the manufacturer.Results. An incremental cost–effectiveness analysis was performed using a case-based approach comparing the cost of progression-free life-year gained. Brentuximab vedotin, already included in the list of vital and essential drugs and provided at the expense of budgetary funds, was chosen as the reference drug. It has been established that the cost of progression-free life-year gained (ICER) with the use of polatuzumab vedotin in combination with rituximab, cyclophosphamide, doxorubicin and prednisolone (R-CHP) in 1st line therapy of adult patients with diffuse large B-cell lymphoma by 60.8 %, or 41.6 million rubles, lower than the cost of progression-free life-year gained when using brentuximab vedotin in combination with doxorubicin, vinblastine and dacarbazine in the 1st line therapy of patients with CD30-positive classical Hodgkin’s lymphoma. Sensitivity assessment showed the stability of the obtained results of clinical and economic analysis to changes in the cost of drugs in compared therapy regimens. The results were sensitive to changes in the efficacy of the compared regimens.Conclusion. The obtained results of the clinical and economic analysis demonstrated that the use of polatuzumab vedotin in combination with rituximab, cyclophosphamide, doxorubicin and prednisolone (R-CHP) in the 1st line therapy of adult patients with diffuse large B-cell lymphoma in the Russian healthcare system is economically appropriate.